Financial stability, regulatory buffers, and economic growth: Some postrecession regulatory implications - Éric Tymoigne (Levy Economics Institute of Bard College, 2010)
Over the past 40 years, regulatory reforms have been undertaken on the assumption that markets are efficient and self-corrective, crises are random events that are unpreventable, the purpose of an economic system is to grow, and economic growth necessarily improves well-being. This narrow framework of discussion has important implications for what is expected from financial regulation, and for its implementation. Indeed, the goal becomes developing a regulatory structure that minimizes the impact on economic growth while also providing high-enough buffers against shocks. In addition, given the overarching importance of economic growth, economic variables like profits, net worth, and low default rates have been core indicators of the financial health of banking institutions. This paper argues that the framework within which financial reforms have been discussed is not appropriate to promoting financial stability. Improving capital and liquidity buffers will not advance economic stability, and measures of profitability and delinquency are of limited use to detect problems early. The paper lays out an alternative regulatory framework and proposes a fundamental shift in the way financial regulation is performed, similar to what occurred after the Great Depression. It is argued that crises are not random, and that their magnitude can be greatly limited by specific pro-active policies. These policies would focus on understanding what Ponzifinance is, making a difference between collateral-based and income-based Ponzi finance, detecting Ponzi finance, managing financial innovations, decreasing competitions in the banking industry, ending too-big-to-fail, and deemphasizing economic growth as the overarching goal of an economic system. This fundamental change in regulatory and supervisory practices would lead to very different ways in which to check the health of our financial institutions while promoting a more sustainable economic system from both a financial and a socio-ecological point of view.
Keywords: E12; E58; G18; G28; Q01; 330; financial crisis; financial regulation; banking supervision; sustainability